The Role of the Traffic Unit Patrol Unit in Preventing Traffic Violations at the Barelang Police - Euro Belmiro Lamza (Advances in Police Science Research Journal, 2021)
The challenges of traffic problems that must be faced are traffic violations, traffic jams, and traffic crimes. Efforts to minimize these violations are prevention. One of the police units that handles traffic problems is the traffic technical function. This study aims to identify and optimize the role of the Barelang Traffic Police in preventing traffic violations and to maximize the implementation of the Traffic Traffic Unit patrols in preventing traffic violations in the Barelang Police jurisdiction. This study is a qualitative research focused on patrols to prevent and minimize traffic violations. The study uses two types of literature, namely research literature which is the result of previous research and conceptual literature that discusses the focus of research from various theories and concepts from experts. The research location which is the source of data for the author is carried out in the jurisdiction of the Barelang Police, especially in the Patrol Unit of the Barelang Police Traffic Unit and in the Batam City area. Based on the results of the research conducted, the implementation of patrols based on management theory has used the appropriate stages, starting from planning, organizing, implementing, and controlling. Meanwhile, based on the traffic police Vademikum book issued by the Directorate of Traffic Police in 2018, there are some things that are rare and have not been implemented. The implementation of traffic patrols carried out by the Barelang Police Traffic Unit Patrol Unit in preventing motor vehicle traffic violations is influenced by several factors consisting of human factors, finance, methods, raw materials, machines and markets. Suggestions from the results of this study are that patrols in the Barelang Police Station prioritize two-wheeled vehicle patrols considering the traffic flow in the Barelang Police Station is quite dense, while improving the quality of human resources can be carried out by empowering members who have carried out the Dikjur to train other members who are have not carried out the training. In addition, activities in carrying out patrols are recommended to be included in the SOP which must be owned by the Barelang Police Traffic Unit.